A plasma focus device as a metallic plasma jet generator. (20th April 2016) - Kasperczuk, A.; Paduch, M.; Tomaszewski, K.; Zielinska, E.; Miklaszewski, R.; Szymaszek, A.
Abstract: This paper aims at a test of a plasma focus (PF) device as a metallic plasma jet generator. The experiment was carried out at the DPF-1000U device in which the inner electrode face was conically shaped. Deuterium (D2 ) with the initial pressure of 0.9 Torr was used as a filling gas. In the experiment, a metallic plasma was ensured due to erosion of the inner electrode during a PF discharge. To create the metallic plasma jet, the eroded copper (Cu) plasma, swept by the deuterium plasma sheath, was accelerated axially and compressed to very small radius (about 1–2 mm). The Cu plasma jet achieved a velocity of 3 × 10 7 cm/s. To study processes of the plasma jet creation and propagation a 16-frame laser interferometer and a four-frame X-ray pinhole camera were used. Recorded images prove a successful adaptation of the PF device to the metallic plasma jet generator.